2017
DOI: 10.1101/231613
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensory and decisional components of endogenous attention are dissociable

Abstract: Endogenously cueing a stimulus for attention enhances sensory processing of the attended stimulus, and efficiently selects information from the attended stimulus for guiding behavioral decisions. Yet, it is unknown if these sensory and decisional components of endogenous attention are under the control of common, overlapping or distinct mechanisms. Here, we tested human observers in a multi-alternative visuospatial attention task with probabilistic spatial cues, whose predictive validity varied across spatial … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…4D). Similar, hemifield-specific effects on biases have not been observed with endogenous cueing (38). Control analyses revealed that neither the benefits in bias at the cued location, nor the correlation of the bias between the Cu and Ip locations, could be attributed to sensory input gain or motoric response bias.…”
Section: Limitations and Extensionssupporting
confidence: 60%
See 4 more Smart Citations
“…4D). Similar, hemifield-specific effects on biases have not been observed with endogenous cueing (38). Control analyses revealed that neither the benefits in bias at the cued location, nor the correlation of the bias between the Cu and Ip locations, could be attributed to sensory input gain or motoric response bias.…”
Section: Limitations and Extensionssupporting
confidence: 60%
“…These are, in order: (i) the cued location (Cu), (ii) the location in an adjacent quadrant, ipsilateral (Ip) or (iii) contralateral (Co) to the cue, and (iv) the location in the quadrant diagonally opposite to the cue (Op). The behavioral responses in the 5x5 contingency table were analyzed with a multidimensional signal detection model, the m-ADC model (36)(37)(38), to quantify psychophysical parameters (sensitivity and bias) at each location. In Figure 1C we show a schematic of a twodimensional (2-ADC) model, for illustrative purposes, although these data were analyzed with a fourdimensional (4-ADC) model (see Methods).…”
Section: A Change Detection Task Protocol: After An Initial Fixationmentioning
confidence: 99%
See 3 more Smart Citations